Driving trajectories in chaotic scattering - Macau, Elbert E. N.; Caldas, Iberê L. (American Physical Society (APS), 2002)
In this work we introduce a general approach for targeting in chaotic scattering that can be used to find a transfer trajectory between any two points located inside the scattering region. We show that this method can be used in association with a control of chaos strategy to drive around and keep a particle inside the scattering region. As an illustration of how powerful this approach is, we use it in a case of practical interest in celestial mechanics in which it is desired to control the evolution of two satellites that evolve around a large central body. © 2002 The American Physical Society.